2016
DOI: 10.1371/journal.pone.0163788
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Mating Compatibility and Competitiveness among Aedes albopictus Strains from Distinct Geographic Origins - Implications for Future Application of SIT Programs in the South West Indian Ocean Islands

Abstract: The production of large numbers of males needed for a sustainable sterile insect technique (SIT) control program requires significant developmental and operational costs. This may constitute a significant economic barrier to the installation of large scale rearing facilities in countries that are undergoing a transition from being largely dependent on insecticide use to be in a position to integrate the SIT against Aedes albopictus. Alternative options available for those countries could be to rely on outsourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 67 publications
1
12
0
Order By: Relevance
“…The latter figure was however obtained in the field 2 and the same strain had a competitiveness of 100% against various field strains under semi-field conditions 3 which are more realistic than “fly vials”. Similarly, a competitiveness of 72–100% was observed for irradiated male Aedes albopictus under semi-field conditions 4 and of 40–80% in another study 5 . These data contradict their claim that “these results suggest that pgSIT has greater potential to eliminate local Ae.…”
supporting
confidence: 52%
“…The latter figure was however obtained in the field 2 and the same strain had a competitiveness of 100% against various field strains under semi-field conditions 3 which are more realistic than “fly vials”. Similarly, a competitiveness of 72–100% was observed for irradiated male Aedes albopictus under semi-field conditions 4 and of 40–80% in another study 5 . These data contradict their claim that “these results suggest that pgSIT has greater potential to eliminate local Ae.…”
supporting
confidence: 52%
“…When considering a regional approach for Aedes control using the SIT, compatibility of strains as well as species may be important as it would allow strains to be imported for release from nearby countries where they can be more easily reared and/or irradiated. Damiens et al [18] demonstrated that male Ae. albopictus from Mauritius and Seychelles islands, about 50-200 km away from La Réunion island, were compatible and could successfully inseminate female Ae.…”
Section: Discussionmentioning
confidence: 99%
“…albopictus at differing ratios of fertile males:irradiated males in both laboratory and field-cage conditions. The study was performed on the Mexican populations of these mosquitoes as irradiated male mating competitiveness can differ between insect populations, so the findings from one region may differ quantitatively or qualitatively from those in geographically distant regions [ 11 , 22 ]. As such, the results of the present study will serve to estimate the minimum required release ratio of sterile males to wild males that could suppress the natural populations of these vectors in a dengue-endemic region of southern Mexico.…”
Section: Introductionmentioning
confidence: 99%